2001
DOI: 10.1021/cm000389p
|View full text |Cite
|
Sign up to set email alerts
|

XAFS Studies of Soft-Heavy-Metal-Ion-Intercalated MxMoS2 (M = Hg2+, Ag+) Solids

Abstract: XAFS studies were performed on two new soft-heavy-metal-ion-intercalated materials M x -MoS 2 (M ) Hg 2+ , Ag + ). For the compound Hg 0.32 MoS 2 , EXAFS results show an average Hg coordination environment consisting of ≈2 S atoms at 2.38 Å and ≈0.2 ((35%) Hg atoms at 2.55 Å. Along with Hg XANES analysis, these data indicate that the Hg atoms in this compound are present as a mixture of mercuric and mercurous ions. Ag EXAFS analysis of the compound Ag 0.61 MoS 2 indicates a Ag coordination environment consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…At low Hg 2+ /W‐DR‐N‐MoS 2 ratio, it was noticed that each Hg 2+ ion exchanged for two H + ions (Equation and Figure a), implying that one Hg 2+ ion probably interacted with two S atoms. The EXAFS curve‐fitting results (Figure c, Figures S18–S20 and Table S6, Supporting Information) gave the first coordination shell of 1.8 sulfur atoms at 2.38 ± 0.02 Å for Hg in the Hg 2+ ‐laden W‐DR‐N‐MoS 2 (ratio: 0.25), revealing that each Hg 2+ indeed interacted with approximately two S atoms . This also plausibly explains the shrinkage of the interlayer spacing and the reduction of the negative charge for the Hg 2+ ‐laden W‐DR‐N‐MoS 2 (Figure b and Figure S17, Supporting Information) normalHxMoS2 + yHgCl2 HgynormalH(x2y)MoS2 + 2ynormalH+ + 2yCl…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…At low Hg 2+ /W‐DR‐N‐MoS 2 ratio, it was noticed that each Hg 2+ ion exchanged for two H + ions (Equation and Figure a), implying that one Hg 2+ ion probably interacted with two S atoms. The EXAFS curve‐fitting results (Figure c, Figures S18–S20 and Table S6, Supporting Information) gave the first coordination shell of 1.8 sulfur atoms at 2.38 ± 0.02 Å for Hg in the Hg 2+ ‐laden W‐DR‐N‐MoS 2 (ratio: 0.25), revealing that each Hg 2+ indeed interacted with approximately two S atoms . This also plausibly explains the shrinkage of the interlayer spacing and the reduction of the negative charge for the Hg 2+ ‐laden W‐DR‐N‐MoS 2 (Figure b and Figure S17, Supporting Information) normalHxMoS2 + yHgCl2 HgynormalH(x2y)MoS2 + 2ynormalH+ + 2yCl…”
Section: Resultsmentioning
confidence: 82%
“…Accordingly, the EXAFS curve‐fitting results revealed that the coordination number of HgS bonding were gradually reduced to 1.1 with the increase of Hg 2+ /W‐DR‐N‐MoS 2 ratios (Figure c, Figures S18–S20 and Table S6, Supporting Information) . In addition, the increased negative charge on Hg 2+ ‐laden W‐DR‐N‐MoS 2 (Figure b and Table S5, Supporting Information) at high Hg 2+ /W‐DR‐N‐MoS 2 ratio suggested the probability of adsorbing counterions for charge neutrality.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among them one may cite the in-situ polymerization of intercalated monomers, the exfoliation of a layered host and subsequent adsorption of polymer and reaggregation, the template synthesis of host structures in polymer-containing solutions, and the direct melt intercalation of polymers into hosts. Though the method of exfoliation and flocculation of Li x MoS 2 have been known for over a decade [21], the mechanism of guest inclusion into MoS 2 is still not well understood [5].…”
Section: Relation To Previous Workmentioning
confidence: 99%
“…Many of these materials have potential applications in heterogeneous catalysis, as superconductors, as ionic or electronic conductors, in reversible battery electrodes, and in waste remediation [5]. These materials generally are comprised of a polymer or organic component (such as optically functional compounds [6]) incorporated between sheets of an inorganic host.…”
Section: Introductionmentioning
confidence: 99%